2018
DOI: 10.1155/2018/2658640
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Central Venous Catheter Malposition in a 10-Year-Old Girl

Abstract: Central venous catheters (CVCs) are placed in operating rooms worldwide via different approaches. Like any other medical procedure, CVC placement can cause a variety of complications. We report the case of an unexpected malposition of a catheter in the right internal jugular vein, where it looped back on itself during placement and went upward into the right internal jugular vein. CVC line placement should always be viewed as a procedure that could become complicated, even in the hands of the most experienced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…As the pushing force increases, kinking of the sheath also increases. Previous reports have shown that the tip of the catheter can travel back to the head during IJV catheterization 13,14 ; however, this does not occur with largebore catheters. 12 We postulate that a 7-Fr catheter would bend into a U shape because it is stiff and that a 9-Fr catheter would kink into a V shape because it is soft.…”
Section: Discussionmentioning
confidence: 96%
“…As the pushing force increases, kinking of the sheath also increases. Previous reports have shown that the tip of the catheter can travel back to the head during IJV catheterization 13,14 ; however, this does not occur with largebore catheters. 12 We postulate that a 7-Fr catheter would bend into a U shape because it is stiff and that a 9-Fr catheter would kink into a V shape because it is soft.…”
Section: Discussionmentioning
confidence: 96%
“…The most possible explanation for the malfunction of these central venous lines is related with the fact that the negative intraluminal pressure due to suction is responsible for collapse of the walls of the offending vessel, which, in comparison with the superior vena cava, has a smaller internal diameter and a weaker vessel wall. Nevertheless, the existence of appropriate suction is not equivalent with correct catheter placement 24 . On the other hand, every case that is characterized by resistance or difficulty in the advancement of the catheter tip should be fashioned as a case of inappropriate direction of the catheter tip.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ultrasound techniques is valuable, mainly when we aim to recognize anatomical structures before and during vessel catheterization, as it may reveal thrombosis, stenosis, anatomical variations, findings that merit special consideration in the process of catheterization. Nevertheless, several studies have failed to verify its capacity to prevent all cases of suboptimal catheter tip 24,28 .…”
Section: Prevention Of Suboptimal Placementmentioning
confidence: 99%
“…Resistance during central venous catheter insertion, poor blood aspiration after insertion, excessively high CVP, and abnormal waveform may be indicative of catheter malpositioning 1 , 8 but CVP monitoring was not done which may have missed early detection of malposition.…”
Section: Discussionmentioning
confidence: 99%
“…Central venous catheter (CVC) is inserted in 8% 1 of patients admitted to the hospital; it is technically challenging with known risk and complication. Complication like malposition, arrhythmia, infection, artery perforation, pneumothorax, hemothorax thrombosis has decreased by use of ultrasound during insertion of CVC.…”
Section: Introductionmentioning
confidence: 99%